A widely applicable set of descriptors - Labute, Paul (Journal of molecular graphics & modelling, 2000)
Three sets of molecular descriptors computable from connection table information are defined. These descriptors are based on atomic contributions to van der Waals surface area, log P (octanol/water), molar refractivity, and partial charge. The descriptors are applied to the construction of QSAR/QSPR models for boiling point, vapor pressure, free energy of solvation in water, solubility in water, thrombin/trypsin/factor Xa activity, blood-brain barrier permeability, and compound classification. The wide applicability of these descriptors suggests uses in QSAR/QSPR, combinatorial library design, and molecular diversity work.